Development of LED-based standard source for total luminous flux calibration. (October 2019) - Nakazawa, Y; Godo, K; Niwa, K; Zama, T; Yamaji, Y; Matsuoka, S
For total luminous flux calibration by a sphere-spectroradiometer system in 2π geometry, a new LED-based standard light source (standard LED) covering the full visible wavelength range has been developed. The developed standard LED has sufficient spectral power over the full visible wavelength range using UV-LED dies of different peak wavelengths in combination with red, green and blue phosphors. By evaluating spectrum flatness based on the magnitude of the second derivative, the spectrum of the standard LED was customised to minimise the measurement uncertainty. Properties of the standard LED such as the luminous intensity distribution, stability and reproducibility were also evaluated. The evaluation results indicate that the standard LED has good properties as a standard light source for the 2π total spectral radiant flux scale. Furthermore, the result of an operating current dependence suggests that the standard LED has benefits as a standard source that conventional standard lamps do not have.